Antenna Concept for an Automotive Radar Sensor at 150 GHz - Köhler, Mike; Schür, Jan; Schmidt, Lorenz-Peter (IEEE Radio Wireless Week 2013, 20-23 Jan., 2013)
Current Automotive Radar sensors operate in a frequency range up to 81 GHz to provide distance, velocity and angle information about traffic objects. For detecting weakly reflecting objects in presence of a nearby strong reflector (e.g. a person standing close to a van) there are high demands on a radar systems angular resolution. A possibility to improve the angular resolution is increasing the operation frequency. In this paper an antenna concept at 150 GHz is presented showing the benefits of high resolution radar for cars. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.antenn

Automotive Radar Frequencies above 100 GHz and Their Advantages (W24) - Köhler, Mike; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.automo

Feasibility of Automotive Radar at Frequencies beyond 100 GHz - Köhler, Mike; Hasch, Juergen; Bloecher, Hans Ludwig; Schmidt, Lorenz-Peter (International Journal of Microwave and Wireless Technologies, 2012)
Radar sensors are used widely in modern driver assistance systems. Available sensors nowadays often operate in the 77 GHz band and can accurately provide distance, velocity, and angle information about remote objects. Increasing the operation frequency allows improving the angular resolution and accuracy. In this paper, the technical feasibility to move the operation frequency beyond 100 GHz is discussed, by investigating dielectric properties of radome materials, the attenuation of rain and atmosphere, radar cross-section behavior, active circuits technology, and frequency regulation issues. Moreover, a miniaturized antenna at 150 GHz is presented to demonstrate the possibilities of high-resolution radar for car
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.LEH.feasib

Feasibility of automotive radar at frequencies beyond 100 GHz - Köhler, Mike; Hasch, Juergen; Bloecher, Hans Ludwig; Schmidt, Lorenz-Peter (International Journal of Microwave and Wireless Technologies, 2013)
Radar sensors are used widely in modern driver assistance systems. Available sensors nowadays often operate in the 77 GHz band and can accurately provide distance, velocity, and angle information about remote objects. Increasing the operation frequency allows improving the angular resolution and accuracy. In this paper, the technical feasibility to move the operation frequency beyond 100 GHz is discussed, by investigating dielectric properties of radome materials, the attenuation of rain and atmosphere, radar cross-section behavior, active circuits technology, and frequency regulation issues. Moreover, a miniaturized antenna at 150 GHz is presented to demonstrate the possibilities of high-resolution radar for car
lhft_intern.bib::Koehler2012